2023
DOI: 10.3390/polym15214233
|View full text |Cite
|
Sign up to set email alerts
|

Switchable Deep Eutectic Solvents for Lignin Dissolution and Regeneration

Debao Li,
Letian Qi,
Mengru Yang
et al.

Abstract: Deep eutectic solvents (DESs) are promising for lignin dissolution and extraction. However, they usually possess high polarity and are difficult to recycle. To overcome this drawback, a variety of switchable ionic liquids (SILs) composed of 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) and alcohols was synthesized and screened. According to the thermodynamic modeling suggestions, the selected DBU–HexOH SIL was coupled with hydrogen-bond donors to form switchable-DES (SDES) systems with moderated viscosity, conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…To understand the structural changes of lignin after degumming hemp fibers, NMR analysis was used, which showed that the main interunit bonds in lignin were bonds β-O-4, β-5, and β-β(Table 1). In summary, most β-O-4 linkages and all β-5 linkages were degraded after degumming [46,47].…”
Section: Fractionation Of Lignocellulosic Materials Using Des-like Mi...mentioning
confidence: 91%
“…To understand the structural changes of lignin after degumming hemp fibers, NMR analysis was used, which showed that the main interunit bonds in lignin were bonds β-O-4, β-5, and β-β(Table 1). In summary, most β-O-4 linkages and all β-5 linkages were degraded after degumming [46,47].…”
Section: Fractionation Of Lignocellulosic Materials Using Des-like Mi...mentioning
confidence: 91%